Synergistic activity of granulocyte-macrophage colony-stimulating factor and 3'-azido-3'-deoxythymidine against human immunodeficiency virus in vitro. - Hammer, S M (1987)
The ability of granulocyte-macrophage colony-stimulating factor (GM-CSF) and 3'-azido-3'-deoxythymidine (AZT) to inhibit human immunodeficiency virus (HIV) in the U-937 monocytic cell line was examined. Acutely HIV-infected U-937 cells were exposed to GM-CSF (0.03, 0.3, 3.0, or 30.0 U/ml) and AZT (0.1, 1.0, or 10.0 microM) alone and in combination for 14 to 17 days. Reverse transcriptase activity in the supernatant, the percentage of cells expressing viral antigens by indirect immunofluorescence, and the 50% tissue culture infectious dose per milliliter of supernatant were determined to assess the level of viral replication in treated and control cultures. By the fractional-product method of analysis, nearly all combinations of GM-CSF and AZT synergistically inhibited HIV replication by these three measurements. The most effective combinations were 30 U of GM-CSF per ml with 0.1, 1.0, or 10.0 microM AZT. These treatments resulted in no reverse transcriptase activity in the supernatants, less than 1% immunofluorescent positive cells, and less than 8 50% tissue culture infectious doses per ml in the absence of cytotoxicity. Despite this degree of suppression, productive viral replication returned in all cultures within 4 to 10 days after drug removal. Combined therapy with GM-CSF and AZT merits consideration in the approach to HIV-associated illnesses.